2019
DOI: 10.1111/gbb.12545
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of proprioceptive movement and mechanical nociception in Drosophila melanogaster larvae lacking Ppk30, a Drosophila member of the Degenerin/Epithelial Sodium Channel family

Abstract: The mechanosensory neurons of Drosophila larvae are demonstrably activated by diverse mechanical stimuli, but the mechanisms underlying this function are not completely understood. Here we report a genetic, immunohistochemical, and electrophysiological analysis of the Ppk30 ion channel, a member of the Drosophila pickpocket (ppk) family, counterpart of the mammalian Degenerin/Epithelial Na+ Channel family. Ppk30 mutant larvae displayed deficits in proprioceptive movement and mechanical nociception, which are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…We specifically looked for contigs orthologous to mechanosensitive genes described so far in D. melanogaster (Karkali and Martin-Blanco, 2017): the putative metazoan mechanotransduction channels, i.e. degenerin/epithelial Na + channel C (DeG/eNaC) (Adams et al, 1998;Gorczyca et al, 2014;Guo et al, 2014;Jang et al, 2019;Tsubouchi et al, 2012;Zhong et al, 2010), the transient receptor potential (TRP) channels (Cheng et al, 2010;Gong et al, 2004;Göpfert et al, 2006;Tracey et al, 2003;Tsubouchi et al, 2012;Walker et al, 2000), the two-pore domain K + channel proteins (K2P) (Tabarean and Morris, 2002), as well as piezo (Kim et al, 2012), piezo-like (pzl) (Hu et al, 2019) and transmembrane channel-like (tmc) genes (Guo et al, 2016).…”
Section: Conserved Set Of Transcripts Associated With Mechanotransduction In Drosophila Terminaliamentioning
confidence: 99%
See 1 more Smart Citation
“…We specifically looked for contigs orthologous to mechanosensitive genes described so far in D. melanogaster (Karkali and Martin-Blanco, 2017): the putative metazoan mechanotransduction channels, i.e. degenerin/epithelial Na + channel C (DeG/eNaC) (Adams et al, 1998;Gorczyca et al, 2014;Guo et al, 2014;Jang et al, 2019;Tsubouchi et al, 2012;Zhong et al, 2010), the transient receptor potential (TRP) channels (Cheng et al, 2010;Gong et al, 2004;Göpfert et al, 2006;Tracey et al, 2003;Tsubouchi et al, 2012;Walker et al, 2000), the two-pore domain K + channel proteins (K2P) (Tabarean and Morris, 2002), as well as piezo (Kim et al, 2012), piezo-like (pzl) (Hu et al, 2019) and transmembrane channel-like (tmc) genes (Guo et al, 2016).…”
Section: Conserved Set Of Transcripts Associated With Mechanotransduction In Drosophila Terminaliamentioning
confidence: 99%
“…Among genes whose expression is completely shared among the four species there are three DeG/eNaC proteins (which in Drosophila are commonly referred to as pickpocket proteins): ppk, rpk, and ppk26 (Adams et al, 1998;Gorczyca et al, 2014;Tsubouchi et al, 2012;Zhong et al, 2010). Only transcripts encoding a fourth pickpocket protein (ppk30), which has been recently related to mechanotransduction in D. melanogaster (Jang et al, 2019), are absent in all samples. Also piezo, its paralog pzl, as well as shaker and painless (pain) have a presence-absence pattern conserved across species.…”
Section: Conserved Set Of Transcripts Associated With Mechanotransduction In Drosophila Terminaliamentioning
confidence: 99%
“…Ppk1 and ppk26 have the same signaling pathway to regulate mechanical nociception, and they do not have functional response to in thermal stimulus ( Gorczyca et al, 2014 ). Ppk30 as a member of the Drosophila Ppk family is detected by class IV multidendritic neurons, and has a role in mechanosensation, but not in thermosensation ( Jang et al, 2019 ).…”
Section: The Role Of Pain-related Genes In Regulating Nociception/painmentioning
confidence: 99%
“…Phylogenetic analysis revealed that Ppk19 belongs to the subfamily that includes Ppk30 (Fig. 1 A), which was previously shown to be required for mechanical nociception and larval movement 11 . This prompted us to examine whether Ppk19 might form ion channels with functions similar to those of Ppk30.…”
Section: Resultsmentioning
confidence: 94%
“…Proteins of the Ppk family (and the broader Deg/ENaC family) function as homotrimers or heterotrimers, suggesting there may be additional Ppk channels involved in mechanosensation in mdIV neurons. Genetic analysis identified Ppk26 and Ppk30 as also expressed in mdIV neurons, and furthermore that they have roles identical to Ppk1 with respect to mechanosensation 8 11 . Here we identify Ppk19 as a new family member dedicated to mechanosensation in mdIV neurons.…”
Section: Introductionmentioning
confidence: 95%